Spatial variability of disease incidence and mortality in the sea fan Gorgonia ventalina in Puerto Rico (Alcyonacea: Goorgoniidae) - Zuluaga-Montero, Anabella (2012)
Populations of the common sea fan (Gorgonia ventalina) were decimated by an aspergillosis outbreak throughout the Caribbean two decades ago. Since then, aspergillosis has been considered as the principal cause of mortality in sea fans. However, prevalence and presumably incidence of this disease have been declining in the Caribbean since the mid 1990s. Incidence indicates new cases of disease in previously healthy colonies, while prevalence indicates percent of diseased colonies at a given sample. Most coral disease studies use preva- lence rather than incidence to assess the temporal dynamics of diseases. Nevertheless, conclusions based only on prevalence should be handled carefully to avoid misinterpretation. This study was carried out at six reefs in Eastern Puerto Rico. We monitored a total of 448 colonies to (1) obtain estimates of incidence and prevalence of disease and other types of lesions, and (2) to determine causes of sea fan mortality plus their spatial and temporal variation. Three transects (10x1m) were haphazardly placed at each study site. At each transect, every colony was numbered and photographed and its height measured to the nearest cm. Transects were monitored at six months intervals and health status of the colonies was recorded. Also, the colonies were divided into height classes (small, medium and large) for incidence, prevalence and mortality analyses. Incidence and prevalence of disease were low in all reefs, suggesting that disease currently plays a minor role in the regulation of sea fans populations. Detachment was the main cause of mortality, and size structure data suggest that recruitment may compensate for mortality rates in two of the reefs. Spatial differences in size structure and density may be related to environmental and physical characteristics at the reef scale that allow sea fans to reach a safe colony size.